Technical report: modelling of stage-based distribution for Loggerhead sea turtle (Caretta Caretta) by Lefkovitch Matrix / Khairun Faraha Ahmad Salim, Najah Nadhira Dorohid and Raja Nur Syaidatul Raja Brahim - Ahmad Salim, Khairun Faraha; Dorohid, Najah Nadhira; Raja Brahim, Raja Nur Syaidatul (2017)
As the population of the most endangered marine species have approaches extinction, thus the proper conservation efforts should be implemented to avoid this problem from getting worse. Lack of age details, particularly for turtle species had triggered the development of Lefkovitch Model. In this paper, we used Lefkovitch stage class model by referring to stage-based life table of Loggerhead sea turtle generated by Crouse (1985) in order to determine which stage gives the most impact on unbalance population of this threaten sea turtle. The population projections obtained are used to examine the population growth rate that reflect the stage at the population changes.